Insights Into the Peroxisomal Protein Inventory of Zebrafish - Kamoshita, Maki; Kumar, Rechal; Anteghini, Marco; Kunze, Markus; Islinger, Markus; Martins dos Santos, Vítor; Schrader, Michael (Frontiers in Physiology, 2022)
Peroxisomes are ubiquitous, oxidative subcellular organelles with important functions in cellular lipid metabolism and redox homeostasis. Loss of peroxisomal functions causes severe disorders with developmental and neurological abnormalities. Zebrafish are emerging as an attractive vertebrate model to study peroxisomal disorders as well as cellular lipid metabolism. Here, we combined bioinformatics analyses with molecular cell biology and reveal the first comprehensive inventory of D. rerio peroxisomal proteins, their association with peroxisomal metabolic pathways and comparison to human peroxisomes. Furthermore, we identified and analysed the peroxisomal targeting signals. Our findings confirm the suitability of zebrafish as a vertebrate model for peroxisome research and open possibilities for the study of novel peroxisomal candidate proteins in zebrafish and humans.